Agricultural growth and industrial development in Punjab - Bhalla, G. S. (International Food Policy Research Institute, 1995)
Punjab has achieved remarkable growth since independence and is now the richest state of India. This growth and prosperity are primarily the result of Punjab's adoption of new technology in agriculture. Its cultivators were the first to adopt the Borlaug seed-fertilizer technology during the mid-1960s, and within a few years the state became the symbol of a green revolution in India.